New technology reveals the role of giant larvaceans in oceanic carbon cycling - Katija, Kakani (Sci Adv, 2017)
To accurately assess the impacts of climate change on our planet, modeling of oceanic systems and understanding how atmospheric carbon is transported from surface waters to the deep benthos are required. The biological pump drives the transport of carbon through the ocean’s depths, and the rates at which carbon is removed and sequestered are often dependent on the grazing abilities of surface and midwater organisms. Some of the most effective and abundant midwater grazers are filter-feeding invertebrates. Although the impact of smaller, near-surface filter feeders is generally known, efforts to quantify the impact of deeper filter feeders, such as giant larvaceans, have been unsuccessful. Giant larvaceans occupy the upper 400 m of the water column, where they build complex mucus filtering structures that reach diameters greater than 1 m. Because of the fragility of these structures, direct measurements of filtration rates require in situ methods. Hence, we developed DeepPIV, an instrument deployed from a remotely operated vehicle that enables the direct measurement of in situ filtration rates. The rates measured for giant larvaceans exceed those of any other zooplankton filter feeder. Given these filtration rates and abundance data from a 22-year time series, the grazing impact of giant larvaceans far exceeds previous estimates, with the potential for processing their 200-m principal depth range in Monterey Bay in as little as 13 days. Technologies such as DeepPIV will enable more accurate assessments of the long-term removal of atmospheric carbon by deep-water biota.